STUDY OF THE POTENCIAL NANOBENTONITE AS AN ADSORBENT IN CATFISH OIL CLARIFICATION PROCESS AND THE DEVELOPMENT OF CATFISH OIL FORMULATION IN TOPICAL NANOEMULGEL DOSAGE FORM - Anita Sari, Tri
Burns are defined as tissue damage caused by heat or corrosive chemicals. Catfish oil contains DHA which has activity as burn wound healing. However, catfish oil has a fishy odor, so it needs additional process to improve the organoleptic properties. This work was aimed to investigate the potency of nanobentonite as an adsorbent to improve catfish oil organoleptics and then develop it into topical nanoemulgel as an alternatif natural wound healing agent. Catfish oil was characterized for its organoleptic, viscosity and fatty acids profile. The nanoemulsion was prepared with self-nanoemulsification method using composition of catfish oil, cremophor RH40 and pEG 400 with various ratio. Evalution of the nanoemulsion included particle size, PDI, zeta potensial, pH, centrifugation test, stability test and morphology. The optimum nanoemulsion was incorporated into hydrogel which was developed by using various gelling agent. Then, the nanoemulgel was evaluated for particle size, PDI, pH, viscosity, spreadability, rheology and stability test. In addition, in vivo skin irritation test of nanoemulgel was studied. Nanobentonite in 10% with size 508,47 ± 10,47 nm was able to improve catfish oil organoleptics without significantly reducing DHA levels. The optimum nanoemulsion was produced by catfish oil, cremophor RH40 and PEG 400 with ratio 1:8:1. The result of nanoemulsion characterization include globule size 21,03 ± 0,23 nm; PDI 0,269 ± 0,04; pH 6,83 ± 0,02 and zeta potential -15 ± 2,57 mV. The optimum nanoemulgel was produced by adding 2% CMC-Na. The evalutation results of nanoemulgel include particle size of 114,4 ± 2,40 nm; PDI 0,399 ± 0,02; pH 6,89 ± 0,01, viscosity 5.700 ± 50 cps, spreadability 5,69 ± 0,08 cm and physicochemically stable under storage condition of 25°C. Rheological study confirmed thixotropic behavior and did not show skin irritation of all rabbits. Thus, nanobentonite is a promising adsorbent to improve catfish oil organoleptic and nanoemulgel is promising carrier for the topical delivery system of catfish oil.